The use of nitrogen timing and nitrification inhibitors as tools in corn and wheat production in Kansas - Foster, Timothy J. (Kansas State University, 2014)
World population, together with the cost of crop production inputs, is increasing rapidly. The current seven billion people on earth are expected to reach nine billion by 2050 with resulting demands on world food production. In addition, the quality of our environment is being impacted by human activities, including agricultural production and crop fertilization. Nitrogen (N) management is the process of applying N fertilizers in a way to maximize use of N by crops, while minimizing loss to the environment. It is becoming imperative, as a means of increasing crop yields and food supplies, while reducing input usage, and minimizing the impact of N fertilization on the quality of our environment, that improved N application practices be identified and utilized. The objectives for this study were to compare the timing of anhydrous ammonia (AA) fertilizer N applications, fall and spring, with and without two different nitrification inhibitors (NI) as possible tools to enhance yield and Nitrogen Use Efficiency (NUE) in corn (Zea mays) and winter wheat (Triticum aestivum L.) in Kansas. Two different nitrification inhibitors were tested as alternatives, N-Serve (nitrapyrin) produced and marketed by Dow AgroSciences, and an experimental product under development by Koch Agronomic Services LLC. Three differing rates of the experimental product were used to assist in determining the optimal rate for this product. The study was conducted over two growing seasons, 2012 and 2013, which differed significantly in rainfall, rainfall distribution, and resulting NUE. Experiments were established at three sites for both crops in both years, on sites/soils selected for differing potentials for N loss, and mechanisms of N loss. One site was established at the Kansas State University Agronomy North Farm (N Farm), where yield potential was high, and N loss potential was low. A second site was established under irrigation at the Kansas River Valley Experiment Field near Topeka, KS (KRV), on a coarse silt loam soil with high potential for N loss through leaching. The third site was established at the East Central Kansas Experiment Field near Ottawa KS (ECK), on a clay pan soil with a high potential for denitrification loss. Weather conditions together with soil characteristics played a major role in the performance of N timing applications and impacted the response to the use of the inhibitors. In low N loss environments such as the N Farm, fall applications of AA to increase spring time-availability for producers showed minimal negative effects on yield or NUE. When combined with a nitrification inhibitor in the fall, performance was similar to spring application for both corn and wheat. At the KRV site leaching loss or potential loss from fall application was high for corn and wheat in both years, however little impact on NUE with NI use was observed. At the high ECK denitrification site, there was only one N loss potential event leading to inhibitor performance at Ottawa in corn in 2013.
Keywords: Nitrogen; Anhydrous ammonia; Nitrification inhibitors; N-Serve; Agronomy (0285)